Reconstruction of the Concept of Nusyūz in Islamic Law: Perspectives of Religious Figures in Ternate, Indonesia - Alimuddin, Harwis; Djalal, Marini Abdul; Abbas, Abdul Haris; Syatar, Abdul; Haq, Islamul (El-Usrah: Jurnal Hukum Keluarga, 2025)
This research aims to examine and reconstruct the concept of nusyūz and the phrase idribūhunna as found in Surah Al-Nisa (4:34), with particular focus on how these concepts are perceived by religious leaders in Ternate City. The purpose of the study is to offer a more humanistic and contextually relevant interpretation of nusyūz that aligns with the dynamics of modern family life. Methodologically, this study adopts a qualitative approach, combining library research with fieldwork. The library research explores classical Islamic jurisprudence (fiqh) and Qur’anic exegesis (tafsir) related to nusyūz, while the fieldwork involves interviews with community and religious leaders in Ternate City. The data were analyzed using three theoretical frameworks: fiqh al-wāqi‘ (contextual jurisprudence), the theory of ‘urf (custom), and linguistic theory (ma‘nā al-ḥaml). The findings reveal that the interpretations held by many religious leaders continue to be shaped by patriarchal norms, leading to a rigid and gender-biased understanding of nusyūz. This study contributes originality by offering a linguistic and contextual reconstruction of the term, presenting nusyūz as a concept that encompasses broader relational disharmony rather than focusing solely on female disobedience. The implications of this research support the development of a more egalitarian and compassionate Islamic legal framework, particularly in addressing family issues in contemporary Muslim societies.